Juridical Review of The Crime of Human Trafficking Study of Decision No. 176/Pid.Sus/2017/PN.Amb. - Mia Ayu Permatasari; K Kuswardani (Proceeding International Conference Restructuring and Transforming Law, 2024)
This study aims to analyze the legal implications of the District Court's decision based on decision number 176/Pid.Sus/2017/PN.Amb. Human trafficking is an act that is very unlawful especially when committed against women and children. The rampant trafficking that has occurred always makes women and children the target, because the mode used is to seduce and provide lures to victims, which causes an increase in the crime of human trafficking. The research method used is the normative juridical approach method with data analysis techniques, namely descriptive analytics. The results of his research show that the decision Number 176/Pid.Sus/2017/PN.Amb, normatively does not have a significant impact on legal protection for victims, namely girls in cases of human trafficking. The District Court's decision focused on the defendant alone but less focused on the victim. In this court decision, it is quite good in giving punishment to the defendant, however, one of the rights needed by the victim, namely restitution, has not been granted by the panel of judges and does not have any impact on the immaterial losses suffered by the victim. Protection and attention to the interests of victims are seen as the main thing in efforts to protect the law against the crime of human trafficking which is regulated in Law No. 21 of 2007 concerning Eradication of the Crime of Human Trafficking and Law No. 1 of 2023 concerning the Criminal Code which has provided protection to the rights of the perpetrators.